The Utilization of Candle Media to Improve Breathing Engineering on Solfeggio Choir Universitas Negeri Medan - Tobing, Octaviana; Silitonga, Pita HD.; Fiska Gulo, Ningsih Linda (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This study aims to determine the use of wax media to improve breathing techniques at Solfeggio Choir, Universitas Negeri Medan. The purpose of this study is to describe how the use of wax media to improve breathing techniques at Solfeggio Choir Universitas Negeri Medan and to determine the obstacles faced by choir participants. Solfeggio, Universitas Negeri Medan. The theory used is the theory of utilization, vocal techniques, breathing, wax media, and choir. The method used in this research is descriptive qualitative method. The sample in this study was the Solfeggio choir, Universitas Negeri Medan. The data were collected by means of observation, interviews, documentation and literature study. Based on the results of the research conducted, it can be seen that the use of wax media for vocal breathing techniques can accelerate the understanding of members in mastering vocal breathing techniques. The obstacles experienced by the choir participants were difficulty in controlling their breathing, different skill levels of the members when practicing breathing techniques using wax media, and discomfort when using wax for the first time.Â